2020
DOI: 10.1007/s00202-020-01053-z
|View full text |Cite
|
Sign up to set email alerts
|

The influence of eddy currents on the excitation winding impedance of solid and laminated salient pole synchronous machines

Abstract: This work investigates the establishment of steady-state eddy currents in solid and laminated salient poles and rotor rim of synchronous machines due to a periodic excitation voltage. It shows that the presence of eddy currents in the rotor magnetic circuit has the double effect of increasing the excitation winding AC-resistance and decreasing its magnetizing AC-inductance. According to that a simple analytical model is presented in here which allows a rapid rough estimation of the excitation winding AC-resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 8 publications
(20 reference statements)
1
4
0
Order By: Relevance
“…It can be observed that the measured values, as well as the regression straights, superpose for both test conditions. This means that the presence of the armature does not change substantially the damping properties of the rotor winding, which supports a theoretical prevision formulated in [33]. Moreover, a clear common asymptotic tendency of the measured values of R p starting from the kHz range ( σ ≅ 0.7) confirms the suitability of () for representing the winding parallel resistance in the range of the winding resonance frequencies and beyond.…”
Section: Resultssupporting
confidence: 84%
See 3 more Smart Citations
“…It can be observed that the measured values, as well as the regression straights, superpose for both test conditions. This means that the presence of the armature does not change substantially the damping properties of the rotor winding, which supports a theoretical prevision formulated in [33]. Moreover, a clear common asymptotic tendency of the measured values of R p starting from the kHz range ( σ ≅ 0.7) confirms the suitability of () for representing the winding parallel resistance in the range of the winding resonance frequencies and beyond.…”
Section: Resultssupporting
confidence: 84%
“…Table 8 shows that the values of L p and L' p decrease while the frequency increases. This is due to the degaussing effect of the eddy currents in the solid poles mainly [30–33] and to the skin‐ and proximity‐effect in the winding secondarily. In order to catch how strongly the winding inductance and the frequency are negatively correlated, the following simple inductance law has been introduced L p ( f ) = K f γ , where K and γ are constants to be found using the inductance values corresponding to the series resonance frequencies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, using a non-laminated magnetic core would be possible only when the magnetic field is constant, e.g. in the rotor of an electrically excited synchronous motor (EESM) [8,9]. Apart from the magnetic core, such rotor contains also an excitation winding as the other active part, which is supplied with direct current (DC) that excites constant magnetic field.…”
Section: Introductionmentioning
confidence: 99%